Ireland: A New Development Context - Marina Boykova; Mikhail Salazkin (Foresight and STI Governance, 2007)
The unprecedented economic growth in Ireland, which began in 1990 and lasted for a decade, was based on a model of economic development, and characterized by a combination of the three "T" - Technologies, Talents, Tolerance. But yesterday's advantages have lost their relevance as a result of profound global transformations. To preserve and strengthen the position achieved in the new context, the Irish have developed a new strategy, appropriate to existing and future challenges and opportunities. Strategies were based on the identified platform for growth and possible scenarios.